Temu Balik Arsip di Pusat Arsip Balai Bahasa Padang - Khotimah, Isnania Khusnul; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study was (1) describe the archive storage system at the Center for Language Center Archive Padang, (2) describe retrieval system through the file in the Central Records Hall of Languages ​​Padang. Data through observation and interviews with the archivist at the Centre for Language Center Archive Padang. Data collection was done descriptively. The findings of the study are (1) archival storage system conducted at the Center for Language Center Archive Padang is not in accordance with the existing theories of the storage systems based on the system of the subject, system name, system number, chronological system and geographic systems. In doing archival storage system archivist Language Institute Padang just doing storage system based on the incoming and outgoing mail are resulting archives are owned be piled and disorganized and difficult to return were found. (2) through the file retrieval system is not fit for the tools to do the back ground using only archival agenda book where the archive search takes a long time because the archivist should find the files one by one in the diary based on time or archive incoming mail. Keywords: retrieval system; the archive storage